Etika Bisnis dalam Ekonomi Islam - Rizky Andika; Wahyu Akbar Alfarizi; Irhan Irhan; Syarifullah Hidayat; Rivaldi Pranata (Al-Sharf: Jurnal Ekonomi Islam, 2021)
In Islamic economics, business and ethics do not have to be seen as two contradictory things, because business which is a symbol of worldly affairs is also considered an integral part of things that are investments in the hereafter. That is, if the business orientation and investment efforts in the afterlife (intended as worship and are the totality of obedience to God), then business by itself must be in line with moral principles based on faith in the afterlife. In the view of Islam, ethics is a guideline used by Muslims to behave in all aspects of life. This research is a literature study, which will examine business ethics in Islamic economics, according to the literature obtained. From the results of the discussion obtained, Islamic business ethics must be based on the Qur'an and Hadith, where every applicable operation must follow or be based on the Qur'an and Hadith.Keywords: Ethics, Business